Analisis Perbandingan Trading Volume Activity Dan Abnormal Return Saham Idx30 Sebelum Dan Sesudah Pengumuman Covid-19 Sebagai Pandemi Oleh World Health Organization - Permata Sari, Putu Elfira; Dewi, Rencana Sari (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
Capital market conditions are affected by the events that happen around them. One of the events that could affect the capital market condiitons is the announcement of Covid-19 as a pandemic by the World Health Organization. The purpose of this research is to find out whether there is significant difference of Trading Volume Activity and abnormal return for the companies listed on the IDX30 Index before and after the announcement of Covid-19 as a pandemic by the World Health Organization. This research is a quantitative research based on event study with 11 days event window which consist of 5 days before, event day, and 5 days after the events. This research used secondary data that was acquired from the official website of Bursa Efek Indonesia and yahoo finance. The result shows that there is no difference in Trading Volume Activity before and after the announcement ofÂ  Covid-19, meanwhile, in abnormal return, there is a difference between before and after the announcement ofÂ  Covid-19.